Tax Policy : Recent Trends and Coming Challenges - Khan, Tehmina S. (IMF Working Papers; Working Paper, 2007)
This paper provides an overview of the key economic factors that shape tax policy reform in many high-income countries, developing countries, and/or transition economies. The paper describes and evaluates global and regional developments with respect to tax rates and revenue ratios over the last some 20 years, and discusses selected structural reform initiatives that have been high on the policy agenda over this period. In particular, it focuses on developments relating to experiments with the restructuring of corporate tax, the impact of corporate taxes on FDI, key reform initiatives including dual income taxes and flat taxes, as well as the worldwide spread of the VAT and policy developments associated with climate change and natural resource taxation.